2023
DOI: 10.1101/2023.08.20.554009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social complexity affects cognitive abilities but not brain structure in a Poecilid fish

Zegni Triki,
Tunhe Zhou,
Elli Argyriou
et al.

Abstract: Complex cognitive performance is suggested to be the out-turn of complex social life, allowing individuals to achieve higher fitness through sophisticated “Machiavellian” strategies. Although there is ample support for this concept, especially when comparing species, most of the evidence is correlative. Here we provide an experimental investigation of how group size and composition may affect brain and cognitive development in the guppy (Poecilia reticulata). For six months, we reared sexually mature female gu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
3
1
Order By: Relevance
“…Additionally, Triki et al (2022a , 2023b ) found a positive correlation between the size of this brain part and inhibitory control abilities, which was not observed in the current study. One possible reason for this could be that Triki et al’s studies ( 2022a , 2023b ) involved the use of guppies that were selectively bred to reach a divergence in relative telencephalon size over several generations. Often, it is difficult to detect brain morphology effects on behavior in wild-type strains of laboratory-held animals fed ad libitum and where predation selection pressures are removed (see discussion on this topic in ( McNeil et al 2021 )).…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Additionally, Triki et al (2022a , 2023b ) found a positive correlation between the size of this brain part and inhibitory control abilities, which was not observed in the current study. One possible reason for this could be that Triki et al’s studies ( 2022a , 2023b ) involved the use of guppies that were selectively bred to reach a divergence in relative telencephalon size over several generations. Often, it is difficult to detect brain morphology effects on behavior in wild-type strains of laboratory-held animals fed ad libitum and where predation selection pressures are removed (see discussion on this topic in ( McNeil et al 2021 )).…”
Section: Discussioncontrasting
confidence: 91%
“…4c ), but it did not explain performance differences across treatments. Individual-level improvement in reversal learning performance due to larger telencephalon has already been demonstrated in guppies by Triki et al (2022b , 2023b ). Additionally, Triki et al (2022a , 2023b ) found a positive correlation between the size of this brain part and inhibitory control abilities, which was not observed in the current study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The authors show that the presence of parental care affected the population's response to selection. Possible evidence could also concern a recent study showing plasticity in intelligence responding to the group size of residence in guppies (Triki et al 2023).…”
Section: Experimental Evolutionmentioning
confidence: 99%